Interpretasi Kontekstual: Studi Pemikiran Hermeneutika Al-Qur’an Abdullah Saeed - Lien Iffah Naf’atu Fina (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Abdullah Saeed is one of contemporary Muslim thinkers sought to offer an idea to reinterpret al-Qur’an. His offering starts from the rising of the textual interpretation phenomenon. This article tries to discuss Saeed’s offering in interpreting al-Qur’an called a contextual interpretation. This serves as an act to interpret al-Qur’an through considering al-Qur’an context when it was revealed as well as its contemporary context. The focus of Saeed’s interpetation is the ethic-legal verses which become the frequent ‘source of problem’ when Islam faces modernity. To support his interpretation’s idea, Saeed maintains some arguments on the benefit of reinterpretating al-Qur’an. This article views that Saeed’s contextual interpretation served as the continuation and improvement of Fazlur Rahman’ s double-movement. Saeed’s great contribution to Rahman is through a more clear and concise framework of its interpretation particularly on the theory of values hierarchy.